Financial analysis of the leading oil and gas companies in the Russian Federation for 2021 - A. V. Troitsky; O. V. Baykova; V. I. Brents; M. I. Razinkov (Вестник университета)
Oil and gas complex is a common name for a group of industries for the extraction, transportation and processing of oil and gas and the distribution of products of their processing. Oil and gas complex plays a significant role in the development of the economy both in the domestic and foreign markets. The article focuses on the contribution of the industry to the country’s economy, in addition, the resource base of minerals of the Russian Federation is considered. The dependence of the Russian economy on oil and gas is clearly demonstrated. The analysis of the current situation on the oil and gas market is carried out, the impact of the oil and gas complex on the economic indicators of Russia is assessed. The article examines and analyses the leading vertically integrated oil companies. This analysis allows us to see the developing and increasing indicators of companies in terms of progress.